Covid-19 Prevention and Control Effort on Adolescent Women in Dungaliyo District, Gorontalo Regency - Fifi Ishak; Siti Surya Indah Nurdin; Zul Fikar Ahmad; Sasgita Lakadjo; Audia Paramata (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
As a result of COVID-19, the world is facing an unprecedented global health and socioeconomic crisis. This service aims to provide education to the public regarding efforts to prevent and control COVID-19 in the community. The service will be held in December 2021 in Dungaliyo District, Gorontalo Regency. The service is carried out in the form of counseling using the lecture method with the help of Power Point which is then discussed with the participants. The participants of the activity are adolescent women at Dungaliyo District. The implementation of activities is self-funded by the executor. This service activity went well.